The Relationship Between Knowledge of Anemia and Its the Incidence Among Pregnant Women - Abdilla Fi Qisthy Wibowo Qisthy (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: The woman and fetus may suffer from anemia during pregnancy, which can lead to infection, early birth, and maternal and child deaths. Insufficient understanding of anemia is one of the factors contributing to anemia during pregnancy. Pregnant women's attitudes and behaviors to prevent anemia in pregnancy can be impacted by their ignorance of anemia. The purpose of this study was to determine the relationship between knowledge about anemia and its occurrence in pregnant women at Puskesmas Klaten Utara.  Methods: This research is a descriptive analytical study with a cross-sectional approach. The population in this study consisted of pregnant women who were registered and attended antenatal care at Puskesmas Klaten Utara during October–November 2023. A total of 50 respondents who met the inclusion criteria were selected using accidental sampling technique. Data were collected through questionnaires and analyzed using the Spearman Rank correlation test. Results: According to statistical studies, the incidence of anemia in pregnant women at Puskesmas Klaten Utara is correlated with the amount of knowledge about anemia in pregnant women, with a correlation value of 0.442 and a significant value of p-value = 0.001 (p-value <0.05).  Conclusion: There is a significant positive correlation between pregnant women's knowledge and the incidence of anaemia at the North Klaten Community Health Centre. Strengthening anaemia prevention programmes through regular supervision and health education is essential. Midwives are expected to raise awareness and compliance among pregnant women in taking iron tablets to reduce the incidence of anaemia.